2012
DOI: 10.1371/journal.pone.0053166
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Soil Characteristics, Allelopathy and Frugivory on Establishment of the Invasive Plant Carpobrotus edulis and a Co-Occuring Native, Malcolmia littorea

Abstract: BackgroundThe species Carpobrotus edulis, native to South Africa, is one of the major plant invaders of Mediterranean coastal ecosystems around the world. Invasion by C. edulis exerts a great impact on coastal habitats. The low number of native species in invaded communities points to the possible existence of mechanisms suppressing their germination. In this study we assessed whether soil factors, endozoochory, competition and allelopathic effects of the invader affect its own early establishment and that of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 63 publications
3
49
1
1
Order By: Relevance
“…The rate of seed germination decreased in parallel with increasing concentrations of the extract. Previous studies have demonstrated that allelopathic plants can affect the germination indices (G T and A S ) and seedling growth of many target species (Hussain et al 2011;Novoa et al 2012). Increasing the inhibitory effect by altering the extract concentration is in accordance with previous studies (Hussain et al 2011;Gomaa & AbdElgawad 2012).…”
Section: Discussionsupporting
confidence: 89%
“…The rate of seed germination decreased in parallel with increasing concentrations of the extract. Previous studies have demonstrated that allelopathic plants can affect the germination indices (G T and A S ) and seedling growth of many target species (Hussain et al 2011;Novoa et al 2012). Increasing the inhibitory effect by altering the extract concentration is in accordance with previous studies (Hussain et al 2011;Gomaa & AbdElgawad 2012).…”
Section: Discussionsupporting
confidence: 89%
“…The flowers are frequently visited by native pollinators (Bartomeus et al 2008), seed production is particularly abundant, reaching an average of 1000 seeds per fruit (Carta et al 2004; Bartomeus and Vilà 2009), and a high proportion of seeds is stored in the soil seed bank and in litter (Chenot et al 2014). Seed dispersal is then carried out mainly by small mammals such as rats and rabbits, whose ingestion causes an increase in the germination percentage and therefore the chance for new individuals to become established (D'Antonio 1990a;Bourgeois et al 2005;Novoa et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…invasive success (D'Antonio 1990b(D'Antonio , 1993D'Antonio et al 1993;Novoa et al 2012) and to assessing the ecological consequences associated with their invasion on floristic richness and diversity (Carta et al 2004;Vilà et al 2006;Andreu et al 2010;Novoa et al 2013;Chenot et al 2014;Fried et al 2014), on soil properties (Vilà et al 2006;Conser and Connor 2009;de la Peña et al 2010;Santoro et al 2011;Novoa et al 2013 or on both (Vilà et al 2006;Novoa et al 2013). In all previous references, Carpobrotus spp.…”
Section: Introductionmentioning
confidence: 99%
“…Some invaders, such as Carpobrotus edulis, affect the community composition, diversity and succession via modification of the soil properties. It has been shown that the effect of C. edulis on pH and nitrogen compounds persists over time even after Carpobrotus removal (13,14). This suggests a possible allelopathic effect of its litter (14).…”
Section: Vegetation Samplingmentioning
confidence: 99%
“…It has been shown that the effect of C. edulis on pH and nitrogen compounds persists over time even after Carpobrotus removal (13,14). This suggests a possible allelopathic effect of its litter (14). Clonal growth has recently been indicated as an attribute that could contribute to the invasiveness of plants (15,16).…”
Section: Vegetation Samplingmentioning
confidence: 99%